Identification of Critical Success Factors (CSFS) for PPP Scheme Toll Road Projects in Indonesia - Asep Suhana; Pratikso Pratikso; Rachmat Mudiyono (Jurnal Indonesia Sosial Teknologi, 2024)
Public-Private Partnership (PPP) models represent an innovative procurement approach and offer promising prospects for the future of the construction industry worldwide. However, in practice, not all PPP projects, particularly toll road projects, succeed in achieving their goals. This poses a unique challenge in determining the Critical Success Factors (CSFs) as the basis for evaluating project success. Therefore, the aim of this research is to identify and explore the concept of CSFs for toll road projects under the PPP scheme based on reputable academic journals in the last 10 years. This study employs a sequential exploratory mixed methods methodology to identify and explore CSF indicators for PPP scheme projects and to verify and validate the findings. The re-sults of this study reveal 13 indicators crucial for project success, categorized into 8 factors. The findings of this research contribute significantly to the management of PPP toll road projects in Indonesia, serving as a reference for stakeholders in decision-making to enhance the effective-ness and efficiency of toll road project management.